2018
DOI: 10.1186/s40885-018-0102-8
|View full text |Cite
|
Sign up to set email alerts
|

Arterial stiffness and hypertension

Abstract: Measures of the functional and structural properties of blood vessels can be used to assess preclinical stage of vascular disorders. Recent experimental and population studies show that arterial stiffening precedes development of high blood pressure, and can be used to predict future cardiovascular events. Arterial stiffness was also shown to be reversible in several experimental models of various conditions. Since reversing arterial stiffness could prevent development of hypertension and other clinical condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
58
1
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(62 citation statements)
references
References 15 publications
0
58
1
3
Order By: Relevance
“…This finding suggests that peripheral arterial stiffness represented by a high baPWV may accelerate the progression of CKD in patients with type 2 diabetes. Many previous studies have suggested that arterial (or aortic) stiffness is closely related with the risk of mortality and specifically cardiovascular disease, not only in the general population but also in patients with underlying comorbidities such as hypertension and diabetes (6,(8)(9)(10). The CRIC study (Chronic Renal Insufficiency Cohort) revealed that high aortic stiffness increases the risk of chronic kidney disease progression and all-cause death in patients with impaired kidney function (23).…”
Section: Discussionmentioning
confidence: 99%
“…This finding suggests that peripheral arterial stiffness represented by a high baPWV may accelerate the progression of CKD in patients with type 2 diabetes. Many previous studies have suggested that arterial (or aortic) stiffness is closely related with the risk of mortality and specifically cardiovascular disease, not only in the general population but also in patients with underlying comorbidities such as hypertension and diabetes (6,(8)(9)(10). The CRIC study (Chronic Renal Insufficiency Cohort) revealed that high aortic stiffness increases the risk of chronic kidney disease progression and all-cause death in patients with impaired kidney function (23).…”
Section: Discussionmentioning
confidence: 99%
“…(b) oxidative stress and inflammatory factors; 8 and (c) vascular calcifications. 9 However, proteins that promote the arterial stiffening in diabetes and hypercholesterolaemia are less known.…”
Section: Backg Rou N Dmentioning
confidence: 99%
“…Arterial stiffness caused by changes including functional alterations of vascular smooth muscle tone and structural changes in the arterial wall mainly reflects gradual fragmentation and loss of elastin fibers and accumulation of stiffer collagen fibers in the large arteries [4, 5]. Several noninvasive assessments of arterial stiffness, as measured by aortic pulse wave velocity (aPWV) and ankle-brachial index (ABI), are independently associated with all-cause and cardiovascular mortality [6].…”
Section: Introductionmentioning
confidence: 99%